USM, UNCW TO PURSUE ACADEMIC AND RESEARCH COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 15 February 2016 Universiti Sains Malaysia (USM) today welcomed a visit from the delegates of University of North Carolina – Wilmington (UNCW), USA with the aim of discussing and identifying potential areas of mutual interest for academic and research collaborations.